Troponin T and N-terminal pro B-Type natriuretic peptide and presence of coronary artery disease. (May 2015) - Mouridsen, Mette R.; Sajadieh, Ahmad; Carlsen, Christian M.; Mattsson, Nick; Heitmann, Merete; Nielsen, Olav W.
Abstract: Background . We tested the effects of exercise intensity, sampling intervals, degree of coronary artery stenosis, and demographic factors on circulating N-terminal pro B-Type natriuretic peptide (NT-pro-BNP) and cardiac Troponin T (cTnT) in subjects suspected of coronary artery disease (CAD). Materials and methods . A total of 242 subjects referred for diagnostic evaluation of possible CAD had blood samples obtained before, 5 min after, and again 20 h after a symptom-limited exercise test. Results . Totally 40 subjects had CAD with ≥ 50% stenosis, 115 subjects had no stenosis and 87 subjects served as controls. In univariate analysis CAD-subjects had higher median baseline NT-pro-BNP-levels (85.3 ng/L) compared with non-CAD-subjects (41.3 ng/L) and controls (40.1 ng/L), both p < 0.001, but the association disappeared in multivariate analysis adjusted for age and gender. NT-pro-BNP increased similarly after exercise in CAD-subjects, non-CAD-subjects, and controls (median increase 8.14 ng/L) and the increase was positively associated with baseline NT-pro-BNP but not presence of CAD. Median baseline cTnT was 6.25 ng/L in CAD-subjects and 3.00 ng/L in non-CAD-subjects as well as controls, both p < 0.0001. Median ΔcTnT (baseline to 20 h after exercise) was higher in CAD-subjects than non-CAD-subjects and controls (0.62 ng/L vs. 0.0 ng/L, p < 0.001). A linear relationship between ΔcTnT and 'percent of predicted maximal heart rate achieved' was found in subjects with ≥ 70% stenosis ( n = 24, r = 0.4067 p = 0.046). Conclusions . Baseline cTnT and ΔcTnT were found to be independently associated with CAD and also with exercise intensity in stable chest pain subjects. These properties were not identified for NT-pro-BNP.